Surveillance following head, neck, and chest radiotherapy: Thyroid ultrasound monitoring for secondary thyroid malignancy12. Issue 1 (7th September 2012) - Kelly, Caitlin; Rivard, Linda; Salvi, Sharad; Hayani, Ammar; Hopkins, William; O'Brien, Sarah; Martin, Laura; Canner, Jason
Abstract Children who receive head, neck, or chest radiotherapy for various primary malignancies have increased risk for secondary thyroid malignancy. Thyroid nodules are difficult to identify by physical examination and/or laboratory tests. Thyroid ultrasound can detect non‐palpable nodules without adverse side effects. We performed a retrospective chart review of 36 patients who received radiotherapy and underwent thyroid ultrasound. Forty‐seven percent (n = 17) had ≥1 nodule(s) detected. Seven patients underwent thyroidectomy; four of whom were diagnosed with thyroid malignancy. Our study suggests routine use of thyroid ultrasound in high‐risk patients detects subclinical thyroid nodules and potential thyroid malignancy post‐radiotherapy. Pediatr Blood Cancer 2013; 60: 140–142. © 2012 Wiley Periodicals, Inc.